Numerical Simulation of Heat and Mass Transfer in Air-Water Direct Contact Using Computational Fluid Dynamics - Wei, Xing; Duan, Bingbing; Zhang, Xuejun; Zhao, Yang; Yu, Meng; Zheng, Youming (Procedia engineering, 2017)
A simplified model is proposed to analyze the heat and mass transfer process in air-water direct contact using CFD in this study. The geometric model is developed as the hydrodynamically developed airflow flat passes through the water surface in a rectangular duct. The outlet airflow parameters, e.g., the temperature field, the humidity field are obtained as the airflow is laminar or turbulent using CFD. The mesh of the CFD-based model is verified using various meshes produced by ICEM CFD. Experimental data and correlations from the references are used to validate the proposed model. Results show that the proposed model has a relatively high accuracy with average deviation of 0.25 °C for temperature and 4% for relative humidity, compared with the experimental data. The Nu and Sh of simulation results fit well with correlations, with average deviation around ±10% in laminar flow and around ±15% in turbulent flow.